The Influence of Stud Characteristics of Football Boots Regarding Player Injuries - Castillo-Domínguez, Alejandro; Torróntegui-Duarte, Marcelino; Páez-Moguer, Joaquín; Gómez-del-Pino, Álvaro; Cervera-Garvi, Pablo; Mainer-Pardos, Elena; Lozano, Demetrio; García-Romero, Jerónimo (IOAP-MDPI, 2022)
Background: the main aim of this study was to analyze the relationship between sole pattern parameters of football boots with the frequency of injuries that occur in semiprofessional and amateur footballers. Methods: The study sample was composed of 77 male football players. All were at least 18 years old, played at least 10 h per week, gave signed informed consent to take part and properly completed the Visual Analogue Scale. This study analysed data from each player’s medical history, including age, injuries, years of practice, field type and surface condition information. Results: The visual analogic score in semiprofessional players was higher (2.05 ± 2.43) than in amateur players (1.00 ± 1.1). A total of 141 lesions were collected, equivalent to 1.81 injuries for each football player studied (n = 77). The result of the ROC curve indicated that the player’s years of practice could predict significantly (p < 0.05) the presence of lower limb injuries, with an area under the curve of 0.714. Conclusions: This study described the predictive capacity of sole pattern characteristics concerning lower limb injuries in amateur and semiprofessional footballers. Football boot variables associated with the number of studs were associated with foot and ankle overload injuries.
Keywords: Fútbol; Football; Soccer footwear; Team sports; Lower limb injury; Stud; Wellness health